The climate memory of an Arctic polythermal glacier - Delcourt, Charlotte; Van Liefferinge, Brice; Pattyn, Frank; Nolan, Matt (2013)
Knowledge of glacier equilibrium-line altitude (ELA) changes and trends in time is essentialfor future predictions of glacier volumes. We present a novel method for determining trends in ELAchange at McCall Glacier, Alaska, USA, over the last 50 years, based on mapping of the cold–temperatetransition surface (CTS), marking the limit between cold and temperate ice of a polythermal glacier.Latent heat release from percolating meltwater and precipitation keeps the ice column temperate in theaccumulation area. A change from accumulation to ablation zone reduces this heat release, leadinglocally to glacier ice cooling. By mapping the CTS along the whole glacier length using radio-echosounding and employing a thermodynamic model, the timing of the cooling was determined, fromwhich past ELAs were constructed. These are in accord with mass-balance measurements carried out onMcCall Glacier since the 1950s. We show that with a warming climate, McCall Glacier tends to cool ina counter-intuitive way info:eu-repo/semantics/published